Antral follicle responsiveness assessed by follicular output RaTe(FORT) correlates with follicles diameter - Camila Bessow; Rafaela Donato; Tatiane de Souza; Rita Chapon; Vanessa Genro; João Sabino Cunha-Filho (BMC, 2019)
Abstract Background The antral follicle count is a marker of ovarian reserve. Follicular Output RaTe (FORT) evaluates the proportion of follicles responsive to exogenous follicle stimulating hormone (FSH) during controlled ovarian stimulation. Our objective was to evaluate whether the diameter (AFC6: ≤ 6 mm or AFC > 6: > 6 mm) of the follicular cohort could be a predictor for ovarian responsiveness, assessed by FORT, in a prospective cohort with 92 women with IVF indication, regular cycles and no abnormality in both ovaries. Results The mean age (±SD) of the women was 36.03 years (± 3.87 years), the median FORT was 43.30%. We found correlation between the FORT and AFC6 (r = − 0.237, P 0.023) but not between the FORT and AFC > 6 (r = − 0.055, P 0.602). Conclusions The inverse correlation between FORT and AFC6 suggests that those follicles were less responsive to the exogenous FSH.